Interviews with artists as a device for contention and the discursive dispute in the 1960s and 1970s - Almeida, Juliana Gisi Martins de (PORTO ARTE: Revista de Artes Visuais, 2018)
This article proposes to reflect on the role of interviews with artists as a contention device in the interaction between two subjects, considering that the desire to apprehend works of art through their various ways turns the artist’s word into a privileged object. That can be seen by understanding the context of the 1960s/1970s, when a discursive dispute took place in the field of art as artists claim speech spaces. Artists’ words are not the truth about their works, since they are as historically, socially and culturally determined as the works themselves; therefore, interviews can be seen as mechanisms that open meaning-making and expand it in the crossing of internal and external views about artistic practice.